Typical Recommendations For Different Premises - Gulnoza Baratova (International Scientific and Current Research Conferences, 2021)
This paper deals with installation options of electrical sockets and switches. The installation of such parts requires compliance with the conditions for height, distance, and others. The basic rules are relevant for the location and installation of sockets and switches in various rooms, wherein the design of these elements is also important in the living space.